(untitled) (Acta Scientiarum. Biological Sciences, 2015)
Peacock bass, a fish of the genus Cichla, is an exotic species from the upper river Paraná floodplain in which the species Cichla kelberi and C. piquiti have been confirmed, coupled to the specie C. monoculus upstream in the Capivara and Taquaruçu dams. The introduction of this genus has caused negative impacts on the diversity of native species. Current research prospects DNA sequences capable of distinguishing the three species and provide molecular data for the taxonomic characterization of the species in the upper Paraná River basin. Sequencing of nuclear (tmo4c4, dlx2 and bmp4) and mitochondrial (cox1, cytb) loci were done from fish of the three species of the genus Cichla reported in the literature of the upper Paraná River basin. Sequence analysis provided molecular differentiation for the species through the usage of loci cytb, dlx2 and cox1. Since the latter only distinguished C. piquiti from the other Cichla species, the loci bmp4 and tmo4c4 were not adequate to accomplish our aim.